Indirect benefits of D11 motorway for spatial socioeconomic development - Lehovec, František; Brabcová, Miroslava; Vondráčková, Petra; Marada, Miroslav (Univerzita Pardubice, 2010)
For municipalities situated up to 15 minutes of car travel from the D11 motorway between Praha and Hradec Králové, the following characteristics were surveyed: · proportion of commuters to Prague · number of job opportunities in the municipality · unemployment rate in the municipality (4/2008) · transport accessibility (time needed) from the municipality to Prague or to a district town · transport accessibility (time needed) to the nearest exit · theoretical (determined by a model) location potential of the municipality in relation to Prague and to a district town (the power of Prague or a district town expressed by the formula: the number of inhabitants divided by the distance from the town to the surveyed municipality) · total location potential (the sum of both partial location potentials) · municipality potential (total location potential related to the surveyed municipality power, i.e. the number of inhabitants in the municipality) The analysis of the data above produced several fundamental, statistically relevant correlation relations among the surveyed characteristics. The location potential of Prague shows the closest correlation relations. A correlation with 5 other characteristics was proved on the 99% significance level. Based on the relationships thus obtained, we may judge that the potential of Prague has a much higher weight for the surveyed municipalities than the potential of Hradec Králové, and therefore the location in relation to the capital city is much more significant for the municipalities than their location in relation to Hradec Králové.
Keywords: motorway; D11; development